Environmental perception of the residents on the banks of the reservoir Soledade in the state of Paraíba - Carvalho, Aurean de Paula; Rodrigues, Maria Anunciada Nery (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The study of environmental perception is crucial to better understand the relationship man/environment. Thus, the aim of this study was to evaluate the environmental perception of the residents on the banks of the reservoir Soledade, taking into account their expectations, satisfactions and dissatisfactions, judgments and behaviors, in order to support environmental management actions that locality. For both, it was the use of a questionnaire with open and closed questions. The results indicated that environmental awareness among residents surrounding of the reservoir Soledade is very limited, confused, fragmented, requiring great attention of pubic power to better environmental management.